Konsentrasiasap Cair Cangkang Kemiri Terhadap Fisikokimia dan Organoleptik Dendeng Sapi - Aldi Umbu Moki; Yessy Tamu Ina (JURNAL PETERNAKAN SABANA, 2024)
The purpose of this study is to produce a concentration of hazelnut shell liquid smoke as a natural preservative by analyzing water content, Ph, and total phenol which affects organoleptic improvement which includes color, taste, texture, and preference. The method used in this study was a randomized design complete with 5 treatments and 4 repeats so that there were 20 sample units. The placement of the treatment is P0 = as a control for the use of hazelnut shells liquid smoke. P1=soaking meat concentration Liquid Smoke pecan shell 2%. P2=soaking meat concentrate Liquid Smoke pecan shell 4%. P3=soaking meat concentrate Liquid Smoke pecan shell 6%. P4= Soaking meat 8% hazelnut shell liquid smoke concentrate. The variables observed were water content, pH, organoleptic covers (color, taste, texture and preference), and the additional test was testing total phenol. And then Testing the moisture content, pH first tests the normality, if the distribution of normal data is analyzed with Anova at the level of 5%. If the effect is real in the treatment, proceed with the Duncan Double wilaya test. Organoleptic Testing (Color, Taste, Texture and Preference Level), if the distribution of data is abnormal, then nonparametric kruskall wallis tested using SPSS 21. If the results of the crucial walis test differ markedly, then proceed with the Mean Comparison Rank Test. Phenol testing is tested descriptively. The results of the analysis of various showed that. That the use of hazelnut shell smoke with different concentration levels has an effect in lowering water content and pH but can increase panelists' preference for organoleptic (color, taste, texture and preference) in beef jerky. Different levels of liquid smoke concentrations can also increase the total phenol activity.